Determinant Analysis of Employee Competence, Workload, Job Satisfaction, Internal Supervision, and Leadership Style on the Quality of Annual Internal Financial Reports at the Department of Population and Civil Registration of Batam - Fitriyanti, Morina; Susanti, Ervin Nora; Hamta, Firdaus (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The quality of annual internal financial reports is essential for government accountability, yet factors influencing report quality in population administration agencies remain understudied. This study aimed to analyze the influence of employee competence, workload, job satisfaction, internal supervision, and leadership style on financial report quality at the Department of Population and Civil Registration of Batam City. A quantitative explanatory study was conducted using census sampling on 45 employees involved in financial administration. Data were collected through 5-point Likert scale questionnaires and analyzed using multiple linear regression with SPSS version 26. Employee competence (β = 0.425; p = 0.002), internal supervision (β = 0.390; p = 0.004), and transformational leadership style (β = 0.450; p = 0.001) had positive and significant effects on financial report quality. Workload had a significant negative effect (β = -0.315; p = 0.009), while job satisfaction showed a positive but marginally significant influence (β = 0.180; p = 0.081). The model explained 72.5% of variance in financial report quality (Adjusted R² = 0.725; F = 18.45; p < 0.001). Strengthening human resource capacity, internal control systems, and transformational leadership while managing workload distribution are critical for achieving reliable financial reports in compliance with Government Accounting Standards.